The input signal to a carbonate aquifer highlights recharge processes and climate evolution under temperate Atlantic conditions. Issue 8 (11th June 2022) - Cao, Feifei; Jaunat, Jessy; Huneau, Frédéric; Négrel, Philippe; Garel, Emilie; Mattei, Alexandra; Celle, Hélène; Ollivier, Patrick
ABSTRACT: The objectives of this study are to characterize the input signal of a shallow carbonate aquifer in northeastern France and to clarify the recharge and groundwater mineralization processes, by analysing the chemical and isotopic (δ 18 O, δ 2 H) composition of rain and groundwater. The groundwater isotopic signature was very close to the calculated local meteoric water line and showed a narrow range, which is explained by the buffer effect of the matrix-dominated chalk aquifer. Nevertheless, intensive fracture networks can exist at local scale and lead to rapid aquifer response to rainfall, as attested by observed large variations in groundwater isotopic and chemical signatures at one specific site. Main factors controlling the groundwater mineralization are highlighted, including the input signal, water-rock interactions and human activities. Moreover, groundwater isotopic signatures are related to groundwater ages and historical climate conditions, showing that groundwater isotopic signal could also be used as a record of climate changes.